PENGARUH MANAJEMEN LABA, KUALITAS AUDITOR, DAN KESULITAN KEUANGAN PADA KETEPATAN WAKTU PELAPORAN KEUANGAN - Seni, Ni Nyoman Anggar; Mertha, I Made (E-Jurnal Akuntansi, 2015)
This study aims to know the effect of earnings manipulation, quality auditors, and financial distress on the timeliness of financial reporting manufacturing companies located in Indonesia Stock Exchange 2010-2012. The number of companies studied were 37 company for 3 years, so the number of samples were 111 companies. The sample selected based on specific criteria. Using a binary logistic analysis. Results of analysis showed that earnings manipulation , quality auditors, and liquidity as a proxy for financial distress affect the timeliness of financial reporting manufacturing company. However, leverage as a proxy for financial distress had no affect on the timeliness of financial reporting manufacturing company.
Keywords: timeliness,earnings manipulation,quality auditors,financial distress